Clinico-pathological profile and surgical management of tubercular small intestinal obstruction - Choudhary, Lalit; Bhat, Narendra Singh; Shahi, Kedar Singh (International Surgery Journal, 2018)
Background: Small intestinal obstruction is one of the most common abdominal emergencies faced by surgery resident in emergency department. Diagnosis and management of tubercular intestinal obstruction is challenging as underlying pathology is usually obscure and disease is associated with significant morbidity and mortality. The aim of this study is to know the various clinical features; different types of treatment and prognosis of tubercular intestinal obstruction in adult patients in our setting. Our centre is the only tertiary care centre belongs to Kumauni region at present, most of our patient are from low socioeconomical strata of their region. Methods: Our study was a retrospective analytic study. Medical record of all patients who were operated between 2011 and 2016 for intestinal obstruction due to abdominal tuberculosis at Surgery Department of Dr. Sushila Tiwari Government Hospital attached to GMC Haldwani were retrospectively analysed. The patients who were above 14 years of age and operated for obstruction of small bowel and whose complete medical record was available, were included in the study. Results: There were total 59 patients operated during this time span, out of these, 19 were female and 40 were male. Patients from 3’rd decades (37.29%) of their life were most commonly affected. Abdomen pain was most common symptom found in all 59 patients. Ileal Stricture was most common gross finding. Resection anastomosis was done in 71.19%. Conclusions: Most of the cases of abdominal tuberculosis presents with non-specific clinical features, inconclusive laboratory and radiography findings.